1997
DOI: 10.1128/aac.41.12.2797
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose pharmacokinetics of thalidomide in human immunodeficiency virus-infected patients

Abstract: The pharmacokinetics of thalidomide in nine human immunodeficiency virus-infected patients were studied. Single doses of thalidomide were well absorbed, with mean peak concentrations (+/- standard deviations) of 1.17 +/- 0.21 and 3.47 +/- 1.14 microg/ml in the 100- and 300-mg dosing groups, respectively, and the mean elimination half-life was approximately 6 h. Adverse effects were mild, with drowsiness being reported for seven of nine patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…21 The mean elimination halflife, volume of distribution, and total body clearance of thalidomide reported here, assuming complete oral absorption of the drug, were, however, similar to those reported previously in both healthy and diseased states. 21,[24][25][26][27] Our data also indicate that thalidomide would not be expected to accumulate in the body after daily dosing with either 100-or 200-m g doses, as the expected steady state accum ulation ratio was calculated to be about 1.10. This is in agreement with an actual value of 1.20 reported for a group of healthy female volunteers receiving 200 mg of thalidomide daily for 21 days.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…21 The mean elimination halflife, volume of distribution, and total body clearance of thalidomide reported here, assuming complete oral absorption of the drug, were, however, similar to those reported previously in both healthy and diseased states. 21,[24][25][26][27] Our data also indicate that thalidomide would not be expected to accumulate in the body after daily dosing with either 100-or 200-m g doses, as the expected steady state accum ulation ratio was calculated to be about 1.10. This is in agreement with an actual value of 1.20 reported for a group of healthy female volunteers receiving 200 mg of thalidomide daily for 21 days.…”
Section: Discussionmentioning
confidence: 92%
“…24 Studies of healthy volunteers using different oral preparations of thalidomide have reported considerably higher 25 or lower 21 dose-adjusted C m ax coupled with a significantly higher T m ax of 6.4 hr 25-27 and 4.4 hr, 21 although these differences are likely due to the poor solubility of the unspecified preparations used. 21 The mean elimination halflife, volume of distribution, and total body clearance of thalidomide reported here, assuming complete oral absorption of the drug, were, however, similar to those reported previously in both healthy and diseased states.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chen et al 28 reported the pharmacokinetics of thalidomide after oral dosing in healthy male volunteers. The disposition of thalidomide in these patients was characterized by an elimination half-life of approximately 9 h, a clearance of 10 L/h, and an apparent volume of distribution of nearly 121 L. Piscitelli et al 22 reported the pharmacokinetics of thalidomide in HIV-infected patients after a single oral dose. Thalidomide pharmacokinetics in these patients was characterized by slow absorption, with a mean t max of 3.4 h, an elimination half-life of approximately 6 h, an oral clearance of approximately 8.5 L/h, and an apparent volume of distribution of approximately 85 L. For both the studies, the dose was no more than 300 mg. Our study reported nearly identical values for the low-dose arm (200 mg), but the apparent volume of distribution and the halflife were significantly different for the high-dose arm (800 mg test dose and then dose escalations every 2 weeks).…”
Section: Discussionmentioning
confidence: 98%
“…To date, evaluation of the pharmacokinetics of the drug in HIVinfected persons has been restricted primarily to single-dose studies that do not provide data on the pharmacokinetics of the most recent and widely used formulation of the drug (Celgene) under multiple dose conditions in HIV-infected patients [9,10]. Furthermore, some concern exists as to whether thalidomide may induce its own metabolism following chronic dosing [11].…”
mentioning
confidence: 99%